Face Recognition Brain Functional Connectivity in Patients With Major Depression: A Brain Source Localization Study by ERP - Lei, Lei; Zhang, Yu; Song, Xiaotong; Liu, Penghong; Wen, Yujiao; Zhang, Aixia; Yang, Chunxia; Sun, Ning; Liu, Zhifen; Zhang, Kerang (Frontiers in Psychiatry, 2021)
Objective: The patients with major depressive disorder (MDD) have defects in face recognition，which is a fundamental skill required for social interactions. The aim of this study was to investigate whether MDD patients develop facial perceptual processing disorders and present with characteristics of brain FC. Method: Our study used ERP to record differences between depression patients and healthy participants with face and non-face recognition tasks. Results: Amplitude induction by face pictures was higher than that of non-face pictures both in MDD and HC group. Face recognition amplitude in MDD was lower than in HC group. Then we chose these two time periods with significant difference for further analysis. The results showed that FC in the MDD was stronger than in the HC group in more brain regions in both periods. However, there was only one FC between two brain regions in HC was stronger than MDD. Conclusion: Dysfunction in brain FC in MDD patients is a relatively complex phenomenon, exhibiting stronger and multiple connectivity with many brain regions of emotions. Evidence provided in this paper suggests that the brain FC of MDD patients is more complex and less efficient in the initial stage of face recognition.